Social innovation measurement model and overview of a potential regional social innovation development program - Veres Somosi, Mariann; Kocziszky, György (НТУ "ХПІ", 2017)
The relevant international literature pays significant attention on the analysis of territorial (regional) innovation potential, and the requirements of innovation transfer for more than three decades. According the researches there are significant territorial differences also in this dimension; in the peripheral regions the opportunity of catch up (convergence) can be found in social innovation. It is an important issue, what kind of efficiency has social innovation in the peripheries, while the centres can be characterised by high level natural science and service (for example: bank) innovation. The innovation is an important influencing factor which determines the development of centre-periphery relations. According to several empirical analyses, the economic output of the settle ments and regions with outstanding innovation potential is significantly higher also in the converging countries, than this of the territories with the lack of innovation. In the case of the peripheral regions the social innovation can be a good solution for enhancing the economic performance of the territories. In this recent research the authors analyse the role of social innovation and its possibilities in the case of the peripheral regions, hence they think that the catch up of peripheries cannot be a reali ty without significant innovation absorption capacity.
Соціальні інновації моделі вимірювання та огляд потенційних регіональних соціальних інновацій: розробка програми
Keywords: social innovation; peripheries; соціальні інновації; периферії